Decision Making in the System of Representative Government in the Region as an Element of State Control - Marina Vyacheslavovna Isakova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Decision making in the system of representative government public administration as a collective choice. The analysis of the political influence of factions in representative bodies of the system of managerial decision-making using index Shapley - Subika and Banzhaf based on the formalism of simple cooperative games, in relation to the Legislative Assembly of the Leningrad region.